INSTITUTIONAL GOVERNANCE IN RESPONDING TO GLOBALIZATION - Astuty, Eriana; Pratminingsih, Sri Astuti; Suryana, Suryana (Universitas Brawijaya, Indonesia, 2017)
The study was conducted in several private universities in Bandung that already launched a program of internationalization in response to the issue of globalization are increasingly demanding education providers increasingly globally oriented. This study aims to analyze further the factors that drive an institution to improve the quality of teaching, particularly in the preparation of curriculum arrangement and learning plans that meet global orientation by analyzing two variables that allegedly as the drivers, namely institution favorable governance and faculty's global awareness. The research method using descriptive analysis and verificative analysis with IBM SPSS ver. 22 and IBM AMOS ver. 20 as a data processor. The results show that good institutional governance can force lecturers to develop their knowledge and global competence, without any support and strengthening in the form of legitimacy from the institute, is not able to create a globalized learning, and good institutional governance is accompanied by global knowledge and awareness, Can make lecturers a major axis in the creation of a globally oriented learning environment, especially in drafting the curriculum and globalized learning instruction.